"It's the political economy . . .!" A moment of truth for the eurozone and the EU. (12th May 2021) - Dani, Marco; Chiti, Edoardo; Mendes, Joana; Menéndez, Agustín José; Schepel, Harm; Wilkinson, Michael A
Abstract: The article discusses the Weiss dispute from a political economy perspective. It first sets this litigation in its wider context, namely the protracted transformation of the Economic and Monetary Union (EMU) over the last decade, a decade which has revealed the structural flaws in its design. It then briefly sketches the changing role of central banking, from a fixation on fighting inflation to a more recent focus on combating deflation. This helps to explain the problematic character of the Weiss rulings and the commentaries they have provoked, illustrating a general failure to consider the limits of law, the result of clinging to different parts of the EMU wreckage, on the assumption that the current constitutional framework remains viable. Finally, the article emphasizes the transformative potential of the Weiss saga. The judicial conflict lays bare the unsustainability of the present arrangements, and reveals the necessity of a choice between genuinely federal integration and coordinated dismantling of EMU.